DIA-based technology explores hub pathways and biomarkers of neurological recovery in ischemic stroke after rehabilitation - Hu, Wei; Li, Ping; Zeng, Nianju; Tan, Sheng (Frontiers in Neurology, 2023)
OBJECTIVE: Ischemic stroke (IS) is a common disease that causes severe and long-term neurological disability in people worldwide. While rehabilitation is indispensable to promote neurological recovery in ischemic stroke, it is limited to providing a timely and efficient reference for developing and adjusting treatment strategies because neurological assessment after stroke treatment is mostly performed using scales and imaging. Therefore, there is an urgent need to find biomarkers that can help us evaluate and optimize the treatment plan. METHODS: We used DIA technology to screen differentially expressed proteins before and after ischemic stroke rehabilitation treatment, and then performed gene ontology (GO) and pathway enrichment analysis of DEPs using bioinformatics tools such as KEGG pathway and Reactome. In addition, the protein-protein interaction (PPI) network and modularity analysis of DEPs were integrated to identify the hub proteins (genes) and hub signaling pathways for neurological recovery in ischemic stroke. PRM-targeted proteomics was also used to validate some of the screened proteins of interest. RESULTS: Analyzing the serum protein expression profiles before and after rehabilitation, we identified 22 differentially expressed proteins that were up- and down-regulated each. Through GO and pathway enrichment analysis and subsequent PPI network analysis constructed using STRING data and subsequent Cytoscape MCODE analysis, we identified complement-related pathways, lipoprotein-related functions and effects, thrombosis and hemostasis, coronavirus disease-COVID-19, and inflammatory and immune pathways are the major pathways involved in the improvement of neurological function after stroke rehabilitation. CONCLUSIONS: Complement-related pathways, lipoprotein-related functions and effects, thrombosis and hemostasis, coronavirus disease-COVID-19, and inflammation and immunity pathways are not only key pathways in the pathogenesis of ischemic stroke but also the main pathways of action of rehabilitation therapy. In addition, IGHA1, LRG1, IGHV3-64D, and CP are up-regulated in ischemic stroke patients and down-regulated after rehabilitation, which may be used as biomarkers to monitor neurological impairment and recovery after stroke.